2001
DOI: 10.1203/00006450-200111000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Catch-Up Growth Is Associated with Delayed Senescence of the Growth Plate in Rabbits

Abstract: In mammals, release from growth-inhibiting conditions results in catch-up growth. To explain this phenomenon, we proposed the following model: 1) The normal senescent decline in growth plate function depends not on age per se, but on the cumulative number of replications that growth plate chondrocytes have undergone. 2) Conditions that suppress growth plate chondrocyte proliferation therefore slow senescence. 3) After transient growth inhibition, growth plates are thus less senescent and hence show a greater g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
2
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 26 publications
10
86
2
6
Order By: Relevance
“…Accordingly, normalization of cell proliferation in 19 days Dexa-exposed bones was not observed 5 days after cessation of treatment in contrast to bones exposed only for 7 days. Our ex vivo data are in line with the previously published in vivo observation that growth plate chondrocyte proliferation rate is increased upon cessation of systemic glucocorticoid treatment (Gafni et al 2001), previous tamoxifen treatment ( Karimian et al 2008) and hypothyroidism (Marino et al 2008). To our knowledge, it has previously not been demonstrated that elevated proliferation during catch-up growth is attributed to local mechanisms within the growth plate.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, normalization of cell proliferation in 19 days Dexa-exposed bones was not observed 5 days after cessation of treatment in contrast to bones exposed only for 7 days. Our ex vivo data are in line with the previously published in vivo observation that growth plate chondrocyte proliferation rate is increased upon cessation of systemic glucocorticoid treatment (Gafni et al 2001), previous tamoxifen treatment ( Karimian et al 2008) and hypothyroidism (Marino et al 2008). To our knowledge, it has previously not been demonstrated that elevated proliferation during catch-up growth is attributed to local mechanisms within the growth plate.…”
Section: Discussionsupporting
confidence: 91%
“…Apoptotic resting/early proliferative chondrocytes were rare in occasional sections from control animals but after dexamethasone treatment an 18-fold increase was observed. It has been suggested that the observed catch-up growth after dexamethasone treatment is due to delayed senescence of the growth plate as the chondrocytes have undergone fewer replications due to the inhibitory effect of dexamethasone on cell proliferation (Gafni et al 2001). In every dynamic model of growth there are two parameters for optimal growth: cell proliferation and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…A suspensão do tratamento com GC é seguida por um crescimento compensatório 40 , causado, pelo menos em parte, por um mecanismo intrínseco da placa de crescimento 41 Um dos efeitos principais dos GC no osso é diminuir a taxa de formação óssea; esse efeito é reversível, segundo dados obtidos em pacientes após cura de síndrome de Cushing em acompanhamento de longo prazo, através de exames seriados de densitometria por emissão dupla de raio X (DXA) 43 . Essa recuperação ocorre devido à preservação da arquitetura trabecular, mantendo-se, assim, intacto o vigamento no qual os osteoblastos podem sintetizar osso novo, após a suspensão dos GC.…”
Section: Catch-up E Recuperação Da Massa óSsea Após Suspensão Do Uso unclassified